Interpretacja i konsumpcja - Rychlewski, Marcin (Przestrzenie Teorii, 2011)
The author discusses some theoretical problems associated with the description of the modern book market. In particular, he is interested in the release notes and book covers in the context of the literary categories of interpretation and reception. He postulates that the marketing practices of publishers should be called a “manipulative interpretation”, insofar as the information about books and book covers fulfills a double function: that of advertising and affecting the reception of the text. Referring to the two types of interpretation, “exegesis” and “usage”, he believes that the discussed phenomena fall between these two extremes. Both the release notes and book covers are the domain of a limited “usage”, the accuracy of which verifies the market.